Lesions in the oral cavity and esophagus caused by prescribed drugs: A review - Tesic-Rajkovic, Snezana; Radovanovic-Dinic, Biljana (Biomedical papers, 2022)
Almost all drugs, including some plant-based compounds, can have adverse effects, about 10% of which are expressed at the level of the digestive tract and in some cases resemble gastrointestinal diseases. Most commonly manifest as difficult and/or painful swallowing, nausea, vomiting, diarrhea and constipation. In rare cases, lesions caused by medications may be complicated by bleeding, strictures and perforations and can manifest in all segments of the gastrointestinal tract (GIT). The diagnosis is made from a detailed medical history and clinical examination inter alia. and best confirmed by proximal or distal endoscopy.
Keywords: esophagus; drugs; oral cavity; side-effects